Investigations on the fatigue behaviour of welded-in stiffeners with gaps. (February 2022) - Bartsch, Helen; Citarelli, Sandro; Feldmann, Markus
Abstract: The paper deals with investigations on the fatigue resistance of welded-in stiffeners with gaps. The presented investigations aim to specify limits of acceptable imperfections in terms of gaps in welds, as these do not reduce the fatigue strength in all cases. Finite-element simulations applying the effective notch stress concept have been conducted and confronted with fatigue test results from a detailed fatigue test database. Several geometrical influences regarding the fatigue behaviour of welded-in stiffeners with gaps were analysed and evaluated by performing a numerical study. Finally, interesting details of welded-in stiffeners were worked out and presented, in order to be tested experimentally in a future fatigue test program. It can be concluded that the effective notch stress concept is in fact a valuable tool to assess influences on the fatigue behaviour of the presented detail. The weld toe of the stiffener proves to be the relevant failure location in all investigated configurations, the weld root on the other hand is irrelevant. While the section size has a minor influence on the fatigue strength of the welded-in stiffener, the distance of the weld toes is the main influencing characteristic. The gap size does not play a major role for the fatigue resistance, which is why gaps with a certain size could be accepted in practice. This aspect will be confirmed in the future by conducting additional experimental fatigue tests. Graphical abstract: Unlabelled Image Highlights: Collection of an extensive data base on fatigue tests of welded-in stiffeners. Presentation of a comparison of experimental and numerical fatigue test results. Confirmation of notch factors from literature by own investigations. Simulation program to investigate geometry influences of beams with stiffeners on the fatigue resistance.